PELATIHAN OPTIMALISASI KEBERSIHAN DIRI SENDIRI DAN LINGKUNGAN BAGI ANGGOTA PERSEKUTUAN WANITA (PW) KRISTEN WYK 4 GKI GETSEMANI KOTARAJA JAYAPURA - Henderina J. Keiluhu; Melkior Tappy; Elieser Elieser (LPPM Uncen, 2021)
Physical health condition can be achieved in many ways, including the prevention and treatment of diseases, and the maintenance of personal health and the environment around the place of residence. These steps are basic things that can be started from the dissemination of information and knowledge as well as simple practices in the family sphere. This socialization activity featured three matters, namely 1) Socialization about infectious diseases in Papua, 2) Socialization about HIV and AIDS, and 3) Socialization about the use of plants as ingredients for herbal medicines. These three materials are related to personal health and how to get used to living using health protocols, considering that this activity was carried out during the COVID 19 pandemic. The target of the socialization activity was the women members of Wyk 4 GKI Getsemani Kotaraja. These activities were carried out with the socialization method in the form of lectures and discussions as well as practicum. Subsequent practical activities include planting medicinal plants with prepared seeds, followed by visits to the participants to determine the growth of the plants planted during the socialization. The activity took place from 12 August to 2 September 2020. Face-to-face and practical activities could take place well and were successfully attended by 16 participants. The implementation of this activity is expected to encourage and build awareness and concern for improving lifestyles and maintaining body health by regulating a lifestyle according to health rules, proper knowledge of infectious disease materials provided, as well as practicing personal hygiene, especially during the COVID-19 pandemic.